2013
DOI: 10.1039/c3ta00011g
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature proton transport and its effect on thermopower in a solid ionic semiconductor, TTFCOONH4

Abstract: Ammonium proton in a solid ionic semiconductor, TTFCOONH 4 , is shown to be mobile under anhydrous conditions at room temperature by the hydrogen concentration cell method. Isotope substituted TTFCOOND 4 exhibits a 2.2 H/D isotope effect in ion carrier mobility with TTFCOONH 4 . First-principles calculations reveal that an efficient proton-transfer pathway via low-barrier N/H + /N hydrogen bonds reduces the activation energy to 0.12 eV, which is quite small and comparable to that reported in a bulk water syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Evaluation of the curve‐fitting shows that the inclusion of protonic defects is 25 % for TTFCOONH 3 Ph and 20 % for TTFCOOND 3 Ph (see the Supporting Information), that is, one in every four or five molecular pairs includes a protonic defect, respectively. It was thus confirmed that isotope substitution of the ammonium protons has little effect on the doping level in single crystals as well as in powder crystals of TTFCOONH 4 3c. The doping levels determined by the XPS analysis support the results obtained with similar molecular structures containing the TTF moiety and the electrical conductivity of these crystals.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Evaluation of the curve‐fitting shows that the inclusion of protonic defects is 25 % for TTFCOONH 3 Ph and 20 % for TTFCOOND 3 Ph (see the Supporting Information), that is, one in every four or five molecular pairs includes a protonic defect, respectively. It was thus confirmed that isotope substitution of the ammonium protons has little effect on the doping level in single crystals as well as in powder crystals of TTFCOONH 4 3c. The doping levels determined by the XPS analysis support the results obtained with similar molecular structures containing the TTF moiety and the electrical conductivity of these crystals.…”
Section: Resultssupporting
confidence: 77%
“…The number of protonic defects in the two salt‐bridge networks was evaluated to be almost the same by XPS analysis, and so the isotope effect of this ion transport likely originates in the mobility of ion carriers derived from the difference in mass. However, their absolute EMF values are very small, on the 0.1 mV scale, which is almost negligible compared with the theoretical value (inset of Figure 3b), and two orders of magnitude smaller than that of the TTFCOONH 4 system 3c…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…However, there is no report on the single crystalline compound which allows the investigation of structure–property relationship to guide the rational design of such molecular mixed conductors. Although there are several reports on single-crystalline proton–electron mixed conducting ion radical salts, the radical cations in the system exhibit quasi one- or two-dimensional arrangements instead of insulated molecular wire systems.…”
Section: Introductionmentioning
confidence: 99%